Collaborative Supervision: Increasing Teachers' Creativity in the Implementation of Multicultural-based Independent Curriculum - Sahudi, Sahudi; Ma'arif, Samsul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The study aims to describe the success of the collaborative supervision between the head of the madrasah and the teachers at five private madrasah tsanawiyah in Gresik. This research, a qualitative case study design, involved the head of the madrasah and the teachers of five private madrasah tsanawiyah. Instruments used include interviews, observations, and documentation. Data analysis techniques used are data condensation, data presentation, conclusion drawing, and verification. The research findings demonstrate the significant positive impact of collaborative supervision on teachers’ creativity and professionalism and its direct correlation with students' improved learning quality and learning outcomes. Collaborative supervision has been successful in enhancing the creativity of teachers in the implementation of a multicultural-based independent curriculum. The implications of the findings provide a strong basis for educational institutions to consider implementing more effective collaborative supervision strategies in the context of a multicultural-based independent curriculum. The importance of considering cultural and multicultural contexts is also highlighted in designing educational supervision programmes and strengthening the inclusive learning environment.